Pharmacognostical and anitmicrobial studies on Pycreus puncticulatus, (vahl) nees., rhizome - K.P.JAIGANESH,; G.ARUNACALAM, (International Journal of Pharma and Bio Sciences, 2017)
Pycreus puncticulatus, (Vahl) Nees., of Cyperaceae family, is a common weed, found in marshy places throughout India, Srilanka, Peninsula, Cochin and China, which has long been used traditionally for the treatment of various diseases including asthma, hepatitis and respiratory problems. The present investigation is carried out to establish the pharmacognostical standards, which ensures the proper identification and authentication of the plant. This present paper highlights the geomorphology, histo morphology of rhizome, physico-chemical standards, preliminary phytochemical nature and antimicrobial potential of the plant. These observations would be of immense value in the botanical identification and standardization of the drug in crude form and also help to distinguish the drug from its other species.